Analisis Bibliometrik dalam Penelitian Bidang Pendidikan: Teori dan Implementasi - Musyarrafah Sulaiman Kurdi; Muqarramah Sulaiman Kurdi (Departement of Mathematics Education, 2021)
Bibliometrics is an analysis method that uses Mathematical and statistical tools to measure the interrelationships and impact of publications in a particular research area. Bibliometric analysis is a popular method used to analyze large amounts of scientific data and this analysis is rigorous in nature with the aim of exploring that data. The use of this analysis in research allows researchers to uncover the evolutionary nuances of a particular field, while highlighting emerging areas in that field, including the field of education. In this paper, the researcher will use a type of literature research or literature review with the descriptive research method, which is to describe regularly and in detail the data obtained related to the bibliometric method, so that finally the readers get a clear understanding of the descriptions and explanations presented. The focus of this study is on the fundamental question in research methodology, which is what is bibliometric analysis and how is it used in education research? What are the key metrics and indicators used in bibliometric analysis for education research? What are the challenges and limitations associated with using bibliometric analysis in education research? And the final question is what are the best practices for conducting bibliometric analysis in education research?